PENGEMBANGAN ASESMEN DIAGNOSTIK IPAS DALAM KURIKULUM MERDEKA KELAS IV SDN 01 SITIUNG - M. Anggrayni; Amril; Vilda Agustina (STKIP Subang, 2023)
This research is motivated by the use of the science of science diagnostic assessment which is less optimally taught by students. This research aims to produce a valid and practical diagnostic assessment of Science Science class IV in the Merdeka Curriculum at SDN 01 Sitiung. The type of research is research and development. The development model used is the ADDIE model. This research was conducted at SDN 01 Sitiung. The research subjects were class IV teachers and principals of SDN 01 Sitiung. Validity test data obtained through expert validation sheets. Practicality data was obtained through teacher response questionnaires, school principal responses, and teacher mobilization responses.Based on the results of the validity test of three expert validators, the graphic validation score was 91.66%, the content/construct validation score was 77.77%, and the language validation score was 95.42%. So that the average percentage data obtained is 88.42% with a very valid category. The results of the practicality test from the assessment of the response of class IV teachers with a result of 92.85%, the results of the principal's response were obtained 92.85%, the results of the response of the driving teacher were obtained 96.42%. Based on these results, it can be concluded that the IPAS diagnostic assessment in the independent curriculum in class IV at SDN 01 Sitiung that was developed can be declared valid and practical.